Industrial training report: Klinik Idzham / Nur Heidi Eizaleia Shahis Idzman - Shahis Idzman, Nur Heidi Eizaleia (Universiti Teknologi MARA, Negeri Sembilan, 2024)
This report is about my internship experience at Klinik Idzham, which I did from July 22, 2024, to September 13, 2024, mostly in the Human Resources (HR) Department. Even though my main job was to help the HR manager, I also had other duties in different areas that were not typical HR tasks. While working at the clinic, I helped with auditing workflows, created the layout for their upcoming website, made some posters, organised records in the records storage, communicated with third parties to confirm important information and many more. I learnt a lot about the healthcare business and developed important professional skills, such as how to communicate with others in an organisation, keep records, and work with people from other departments. This internship not only made me more flexible in a fast-paced workplace, but it also helped me learn new technical skills and improve my ability to contribute effectively across different roles within an organisation.